Carbon and mercury export from the Arctic rivers and response to permafrost degradation. (15th September 2019) - Mu, Cuicui; Zhang, Feng; Chen, Xu; Ge, Shemin; Mu, Mei; Jia, Lin; Wu, Qingbai; Zhang, Tingjun
Abstract: Arctic rivers export a large amount of organic carbon (OC) and mercury (Hg) to Arctic oceans. Because there are only a few direct calculations of OC and Hg exports from these large rivers, very little is known about their response to changes in the active layer in northern permafrost-dominated areas. In this study, multiyear data sets from the Arctic Great Rivers Observatory (ArcticGRO) are used to estimate the export of dissolved organic carbon (DOC), particulate organic carbon (POC), total mercury (THg) and methylmercury (MeHg) from the six largest rivers (Yenisey, Lena, Ob, Mackenzie, Yukon and Kolyma) draining to the Arctic Ocean. From 2003 to 2017, annual DOC and POC export to the Arctic Ocean was approximately 21612 Gg and 2728 Gg, and the exports of Hg and MeHg to the Arctic Ocean were approximately 20090 kg and 110 kg (0.002% of the total Hg stored in the northern hemisphere active layer). There were great variations in seasonal OC and Hg concentrations and chemical characteristics, with higher fluxes in spring and lower fluxes in winter (baseline). DOC and Hg concentrations are significantly positively correlated to discharge, as discharge continues to increase in response to a deepening active layer thickness during recent past decades. This study shows that previous results likely underestimated DOC exports from rivers in the circum-Arctic regions, and both OC and Hg exports will increase under predicted climate warming scenarios. Graphical abstract: Image 1 Highlights: Average export of dissolved organic carbon and mercury in 2003–2017 were 21612 Gg yr −1 and 20090 kg yr −1 . Organic carbon and mercury have modern and higher flux in Spring, and ancient and lower flux in winter. Discharge significantly correlated with active layer thickness deepening during past decades.